2011
DOI: 10.1177/0003122410395370
|View full text |Cite
|
Sign up to set email alerts
|

Protesting While Black?

Abstract: How does the race of protesters affect how police respond to protest events? Drawing on the protest policing literature and on theories of race and ethnic relations, we explore the idea that police view African American protesters as especially threatening and that this threat leads to a greater probability of policing. We examine more than 15,000 protest events that took place in the United States between 1960 and 1990 and find that in many years, African American protest events are more likely than white pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(44 citation statements)
references
References 95 publications
0
44
0
Order By: Relevance
“…An examination of thousands of SWAT deployment found that blacks and Latinos were much more likely to be impacted by SWAT deployments than whites, and that the disparity was even greater in drug-related search warrants (ACLU 2014). Additionally, in their examination of more than 15,000 protest events that occurred from 1960 to 1990 in the United States, Davenport, Soule, and Armstrong (2011) found that black protesters were more likely than white protesters to draw police presence and that once at events, police were more likely to take action at black protest events. In fact, they found that police were more likely to use force/violence coupled with arrests at black protest events prior to early 1970s, evidencing a "Protesting While Black" phenomenon.…”
Section: Police Repression and Racismmentioning
confidence: 99%
“…An examination of thousands of SWAT deployment found that blacks and Latinos were much more likely to be impacted by SWAT deployments than whites, and that the disparity was even greater in drug-related search warrants (ACLU 2014). Additionally, in their examination of more than 15,000 protest events that occurred from 1960 to 1990 in the United States, Davenport, Soule, and Armstrong (2011) found that black protesters were more likely than white protesters to draw police presence and that once at events, police were more likely to take action at black protest events. In fact, they found that police were more likely to use force/violence coupled with arrests at black protest events prior to early 1970s, evidencing a "Protesting While Black" phenomenon.…”
Section: Police Repression and Racismmentioning
confidence: 99%
“…Scale matters as well. According to previous studies, large protests are more threatening and more likely to lead to repression than small ones (Davenport et al 2011;Earl et al 2003).…”
Section: The Character Of Protest and Repressionmentioning
confidence: 95%
“…Policing, of course, is merely one of a wide array of repressive strategies, but it represents the most public and one of the most common forms of repression (Earl et al 2003). Studying protest policing is critical for enhancing understanding of the relationship between protests and the state, since police embody the objectives of the broader political-economic elite (Davenport et al 2011) and can be 'conceived as "street-level bureaucrats" who "represent" government to people' (Lipsky 1970: 1).…”
Section: Disaggregating Repression and Protestmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research has shown that women activists face intensified levels of public ridicule and invalidation when compared with their male colleagues (Bernal, 2006;Norwood, 2013). Similarly, activists of color cope with intensified hostilities in response to their activism when compared with white activists, including higher levels of criminalization (Davenport et al, 2011) and general violence in response to their activism (Jacobs and Taylor, 2011). In the United States, racial justice activists of color contend with the stressors to which all activists are susceptible while also coping with the impact of structural racism in their lives and in their activism (Gorski, 2019)-an impact from which white racial justice activists are protected.…”
Section: Introductionmentioning
confidence: 99%